A sulfobetaine zwitterionic polymer–drug conjugate for multivalent paclitaxel and gemcitabine co-delivery. (8th June 2021) - Sun, Haotian; Yan, Lingyue; Zhang, Runsheng; Lovell, Jonathan F.; Wu, Yun; Cheng, Chong
Abstract : A zwitterionic polymer–drug conjugate (ZPDC) strategy for the co-delivery of two chemotherapeutics, together with an imaging agent, is reported. Abstract : A zwitterionic polymer–drug conjugate (ZPDC) strategy is developed for the co-delivery of paclitaxel (PTX) and gemcitabine (GEM) chemotherapeutics, as well as a near-infrared fluorescence imaging agent cyanine5.5 (Cy5.5). The well-defined ZPDC is synthesized by tandem azide–alkyne and thiol–ene click functionalization of a biodegradable acetylenyl/allyl-functionalized polylactide and zwitterionic character is conferred by sulfobetaine. It has a number-average molecular weight of 53.6 kDa, comprising 6.5% PTX and 17.7% GEM by weight. Cy5.5 moieties are readily introduced to the ZPDC via conjugation. In aqueous solutions, the ZPDC exhibits a hydrodynamic diameter of 46 nm. In vitro MIA PaCa-2 human pancreatic cancer cells show strong ZPDC cellular uptake and cytotoxicity. In mice, the ZPDC exhibits long blood circulation, effective tumor accumulation, biocompatibility, therapeutic effect, and integrated imaging capacity. Overall, this work illustrates that ZPDCs are promising systems for chemotherapy delivery and bioimaging applications.